Analysis of the process of exporting ecuadorian shrimp to China (Ágora de Heterodoxias, 2023)
In Ecuador, the shrimp sector is considered decisive for the country's economy; due to its sustained growth and participation in the national gross domestic product (GDP), a situation that has allowed it to position itself as the main non-oil export product. The present study seeks to: analyze the process of exporting Ecuadorian shrimp to China, year 2020 - 2021. For this, the methodology used was descriptive and not experimental, the collection techniques used were the application of interviews and the collection of statistical data obtained mainly from official pages such as: Banco Central del Ecuador and the National Chamber of Aquaculture, among other sources. During the pandemic caused by COVID-19, there was a considerable reduction in shrimp exports to China, due to the sanitary security measures implemented globally. However, by the year 2021 the numbers of exports reached historical figures that contributed positively to the reactivation of the country's economy. An important point to note is that it was evidenced that exporting companies who, despite the difficulties presented during the pandemic, due to the return of containers due to the presence of remains of COVID-19 found, never stopped their production, marketing and export activities.
Keywords: international trade; market; trade policy; China; Ecuador